Leaching of zinc from contaminated soil using citrate - Yoo, Kyoungkeun; Park, H.; Lee, K. (2012)
A citric acid leaching test after heavy medium separation process was performed to remove the heavy metal contaminat such as Pb, Cu, and Zn from contaminated soil. The lead component was removed from soil by heavy medium separation whereas zinc component shows 0% - 37.9% removal ratio with particle size. The citric acid leaching was conducted to remove the remained zinc component. The removal ratio of Zn reached to more than 95% under the conditions; 10% in pulp density, 200 rpm in agitation speed, 50 °C, 2 mol/L in citric acid concentration at 2 hrs in leaching time. These results suggest that the heavy medium separation method followed by citric acid leaching is effective for treatment of soil contaminated with various chemical forms of heavy metal.